Legal Protection For Labor Contract In PT. Nawakara Perkasa Nusantara - I Nengah Sugiarta; Maryanto Maryanto (Jurnal Daulat Hukum, 2019)
The problems of this study are: the outsourcing arrangement based on the law applicable and legal protection for contract workers at PT. Nawakara Perkasa Nusantara. Researchers used the method is legal normative juridical approach and specification in this study were included descriptive analysis. Even though sources and types of data in this study are primary data obtained from field studies by interviewing officials and workers in PT. Nawakara Perkasa Nusantara. And secondary data obtained from the study of literature relating to the theory of legal protection and enforcement.Based on the results of research that restrictions or even a rejection of the application of the statutory provisions regarding outsourced workers cannot be done despite how strong workers and unions of the federation units to fight. It is caused by the development of outsourcing itself stating that the areas of specialization, especially in terms of product development expertise of goods and services is growing development. Therefore impact the outsourced workers to work opportunities more widely. Legal protection for contract workers at PT. Nawakara Perkasa Nusantara basically in implementation has not gone as stipulated in the law. The lack of protection regarding the duration of the employment agreement as to which of Article 59 paragraph (2) and (4) which states that PKWT cannot be made to work that is fixed and the period of more than three (3) years, with each year once carried out a contract extension. Interpretation in paragraph (7) stated that the violation of Article 59 paragraph (2) and (4) This will result in the void PKWT turned into PKWTT. In practice, this agreement occurred during the three (3) years with a contract extension once a year. Supposedly workers / laborers in this company have been a permanent employee, when seen from the labor law.Keywords : Protection Law; Labor Contract.